Intertemporal Efficiency and Productivity Changing on Telecommunication Industry (TI) in ASEAN-5 - Wulan Sari, Dyah; Sulistyaningsih, Lusi (Universitas Airlangga, 2021)
The study aims to measure the technical and intertemporal efficiency and find the primary source of productivity change on top three telecommunication firms in each country of ASEAN-5 (Indonesia, Malaysia, Thailand, Philippines, and Singapore) from 2010 to 2016. Data Envelopment Analysis (DEA) bootstrapping with 2000 iterations, DEA window, and Malmquist index are applied to calculate technical efficiency, intertemporal efficiency, and productivity change. The estimation results elucidate that, on average, the technical efficiency of firms is relatively low. On the opposite, the intertemporal efficiency results indicate that the mean efficiency score of each window is high. However, the LDW and LDP tend to be high, showing that the efficiency scores fluctuate. The Malmquist index calculation yields that technological progress possesses a significant contribution to productivity change. Keywords: Technical Efficiency, Intertemporal Efficiency, Productivity Change, Telecommunication Industry, ASEAN-5 JEL: L8, F6, O5, O1, O3